2012
DOI: 10.1111/j.1939-1676.2012.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cyclosporine on Platelet Function and Cyclooxygenase Expression in Normal Dogs

Abstract: Background: Cyclosporine has been shown to alter platelet plasma membranes and have a hypercoagulable effect in humans, leading to thromboembolic complications.Hypothesis/Objectives: Our hypothesis was that by modulating platelet reactivity, cyclosporine increases the risk of thromboembolic complications. The objective was to determine the effects of cyclosporine on primary hemostasis in normal dogs.Animals: Eight healthy, intact female dogs. Methods: A repeated-measures design utilized flow cytometry to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 70 publications
(172 reference statements)
6
15
0
Order By: Relevance
“…In our study, similar to previous studies, the administration of cyclosporine to healthy dogs was not associated with a change in measures of platelet function such as aggregometry or PFA‐100 analysis, or measures of secondary hemostasis such as PT, PTT, and viscoelastometry. These results suggest that any increase in thromboxane was either insufficient to alter platelet function, or that the concurrent increase in prostacyclin synthesis negated any platelet activating tendencies of cyclosporine.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In our study, similar to previous studies, the administration of cyclosporine to healthy dogs was not associated with a change in measures of platelet function such as aggregometry or PFA‐100 analysis, or measures of secondary hemostasis such as PT, PTT, and viscoelastometry. These results suggest that any increase in thromboxane was either insufficient to alter platelet function, or that the concurrent increase in prostacyclin synthesis negated any platelet activating tendencies of cyclosporine.…”
Section: Discussionsupporting
confidence: 90%
“…In dogs with IMHA, cyclosporine is widely used as an adjunctive treatment to corticosteroids . As has been reported in humans, cyclosporine, especially at the time of peak blood drug concentrations, will increase synthesis of thromboxane in dogs in a dose‐dependent manner . Our study demonstrated there was a significant increase in thromboxane synthesis after drug administration.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Ketoconazole has been used to decrease PO cyclosporine dosages in dogs by as much as 75%, although individual responses vary . Experimentally, PO cyclosporine increases some markers of platelet activation in normal dogs, which may be a concern in dogs with IMHA, in which hypercoagulability and thromboembolism may be major contributors to patient mortality . However, the clinical relevance of this phenomenon remains unclear.…”
Section: Results and Recommendationsmentioning
confidence: 99%